Cognitive Function Changes in Older People. Results of Second Wave of Cognition of Older People, Education, Recreational Activities, NutritIon, Comorbidities, fUnctional Capacity Studies (COPERNICUS) - Kujawski, Sławomir; Kujawska, Agnieszka; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Hajec, Weronika; Kwiatkowska, Małgorzata; Skierkowska, Natalia; Husejko, Jakub; Bieniek, Daria; Newton, Julia L.; Morten, Karl J.; Zalewski, Paweł; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Cognitive reserve explains why subjects with more years of education, professional achievement, or participation in recreational activities show less cognitive decline with aging. We hypothesize that levels of recreational travel, education, occupation, systemic health, physical performance and current cognitive activity levels affect the trajectory of cognitive function in older, healthy people in Poland. Materials and methods: N=205 healthy, older people were examined and followed up at two years. Participants completed physical and cognitive function assessments: including the Mini–Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA) and its two subtests Delayed Recall (DR) and Verbal Fluency (VF) and Trail Making Test Part B (TMT B). Factors associated with cognitive functioning were also examined. Results: MMSE result significantly decreased over two years. No significant decrease in other cognitive tests was noted. However, the trajectory of cognitive tests results varied between individual participants. Percentage of variance of change was explained by the following predictors: 21 in MMSE, 24 in MoCA, 8 in DR, 25 in VF and 24 in TMT B. Age and the presence of varicose vein were significantly linked to negative changes in MMSE and MoCA scores, while working in professional occupational status associated with a higher score. The subgroup with varicose veins did worse on the Delayed Recall subtest of MoCA. Conclusion: Cognitive reserve could be extended by proxies of reserve that are related to systemic health and travel activity. The latter is a combination of social, physical and cognitive activity and potentially might serve as an intervention to improve cognitive function in older people. However, due to the limitations of this study, results should be interpreted with caution and needs to be replicated in the further studies.